Oxidative Status and Reproductive Characteristics in Female Cavies (Cavia porcellus L.) Fed on Aqueous Extract of Avocado (Persea americana Mill.) Seed - Nguedia Arius Baulland Dongmo; Bertin Narcisse Vemo; Hervé Tchoffo; Fulbert Aimé Lontio; Brice Menkem; Motchewo Nadège Djuissi; Adamou Mohamadou; Tahir Markhous Adam Mahamat; Margaret Mary Momo Chongsi; Ferdinand Ngoula (Journal of Veterinary Healthcare, 2021)
The present study was initiated to improve the farm animals’ productivity through the use of medicinal plants. More specifically, to determine in female cavies the effects of aqueous extract of avocado seed powder (AEASP) on the estrous cycle, the levels of LH, estradiol and tissues (ovarian and uterine) biomarkers of oxidative stress. For the trial, 24 female cavies with regular estrous cycles were selectedamong 40 trough observation of 4 estrous cycles. They were randomly shared into 4 groups of 6 females each, comparable in term of body weight (bw) (463.60±77.69 g). They received by gavage 1 mL/kg bw of distilled water for the control and 100, 200, 400 mg/kg bw of AEASP respectively for the groups EA100, EA200 and EA400. Subsequently, 3 estrous cycles were studied every day during all the treatment period. At the end, the cavies were slaughtered at the estrus phase; blood, ovaries and uterus were collected for analysis. As result, the AEASP significantly (p<0.05) increase the duration of the estrus phase in females of group EA100, without affecting significantly the duration of the estrous cycle as referred to the control. It significantly reduce the serum level of total cholesterol and increase (p<0.05) the serum concentration of LH in cavies of group EA100 compared to the control. AEASP significantly increase the serum concentration of estradiol in all treated females as referred to the control. It significantly increase the level of malondialdehyde (MDA) in the ovaries of the females of group EA400. In the uterine tissue, superoxide dismutase (SOD) increase significantly in the cavies of group EA200 compare to the control. We can conclude that the AEASP increase the duration of the estrus phase of cavies without affecting the duration of the estrous cycle. Subsequently, it increases the serum concentration of LH and estradiol.
Keywords: Avocado seed